Latest Results from Neutrino Oscillation Experiment Daya Bay - Vorobel, V. (Ukrainian Journal of Physics, 2019)
The Daya Bay Reactor Neutrino Experiment was designed to measure Θ13, the smallest mixing angle in the three-neutrino mixing framework, with unprecedented precision. The experiment consists of eight identically designed detectors placed underground at different baselines from three pairs of nuclear reactors in South China. Since Dec. 2011, the experiment has been running stably for more than 7 years, and has collected the largest reactor antineutrino sample to date. Daya Bay greatly improved the precision on Θ13 and made an independent measurement of the effective mass splitting in the electron antineutrino disappearance channel. Daya Bay also performed a number of other precise measurements such as a high-statistics determination of the absolute reactor antineutrino flux and the spectrum evolution, as well as a search for the sterile neutrino mixing, among others. The most recent results from Daya Bay are discussed in this paper, as well as the current status and future prospects of the experiment.